2019
DOI: 10.1186/s40902-019-0238-9
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of risk factors of oromaxillofacial infection in patients presenting to a hospital emergency ward

Abstract: BackgroundThe purpose of this study was to review the clinical features of oromaxillofacial infections in patients presenting to a hospital emergency ward, to identify the key factors affecting the requirement for hospitalization, and the potential risk factors predisposing to a prolonged length of hospital stay.MethodsA retrospective medical record review of the 598 patients treated for oromaxillofacial infection from 2013 to 2017 at the oral and maxillofacial surgery department, Yangsan Pusan National Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 24 publications
5
15
1
3
Order By: Relevance
“…Most cases in the current study (97.2%) were due to odontogenic causes. This is in accordance with a previous Korean review that reported the rate of maxillofacial infections due to odontogenic infections in Korea to be 92.47% 17 . However, this figure is much higher than those previously documented by other researchers for hospitalized patients of 61.8% to 71.0% 7 , 13 , 14 , 16 , 20 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Most cases in the current study (97.2%) were due to odontogenic causes. This is in accordance with a previous Korean review that reported the rate of maxillofacial infections due to odontogenic infections in Korea to be 92.47% 17 . However, this figure is much higher than those previously documented by other researchers for hospitalized patients of 61.8% to 71.0% 7 , 13 , 14 , 16 , 20 .…”
Section: Discussionsupporting
confidence: 93%
“…Average LOS in this study was 11.47 days. While this is in accordance with studies conducted in South Korea 17,21,22 and other Eastern countries 18,20 , this was a nearly two-to four-fold higher rate than the figures reported for Western populations. A previous study based on national data that investigated the treatment outcomes of patients in the USA admitted with mouth cellulitis reported an average LOS of only 3.9 days 12 .…”
Section: Treatment Outcomessupporting
confidence: 92%
See 3 more Smart Citations